Assortments of Digestive Enzymes Induced in First Instar Larvae of Busseola fusca Feeding on Different Plants. (April 2019) - Juma, Gérald; Le Ru, Bruno; Calatayud, Paul-André
The stem borer Busseola fusca (Fuller) (Lepidoptera: Noctuidae) is an important pest of maize and sorghum in sub-Saharan Africa. This insect has oligophagous feeding habits, feeding mostly on maize and sorghum with a narrow range of wild Poaceous plant species. We hypothesised that first instar B. fusca larvae, the critical stage for successful establishment on a host plant, can establish and then grow on a particular plant as a result of induction of a complement of digestive enzymes that mediates host acceptance at first instars. A fast semi-quantitative analysis of potentially digestive enzymatic activities present in the first larvae previously fed for 4 days on leaves of host and non-host plants was performed using the API-ZYM kit system able to detect a multiplex of enzyme activities. Regardless of the plant species, the larvae exhibited higher activities of the carbohydrate metabolising enzymes than of aminopeptidases and proteases. In addition, highest activities of carbohydrates degrading enzymes were exhibited by larvae that consumed leaves of the most preferred plant species of B. fusca . Conversely, esterases were only detected in neonate larvae that consumed leaves of the less preferred and non-host plants. No alkaline phosphatase and lipase activities were detected. The significance of these results was discussed in terms of food requirements of first instar larvae when settling on a plant.